Development Of Flipbook Teaching Materials Based On Local Wisdom On Environmental And Health Topics In Elementary Schools - Noufan Aditya; Sri Lestari Handayani (Green Publisher Indonesia, 2024)
The purpose of this study was to utilize traditional knowledge to create an environmental health flipbook for fifth grade students of SDN Cijantung 01 Pagi. The method used in this research is Research and Development (R&D) with the ADDIE research model (Analysis, Design, Development, Implementation, and Evaluation). The results of this study show that the local wisdom-based flipbook that has been validated by media experts obtained a score of 86.66% and can be categorized as very feasible, The results of the validation by the material expert obtained a score of 80% which can be categorized as very feasible, and the results of the validation by language experts with a score of 100%. The teacher's response to the aspects of material, learning, and media obtained a score of 100% and the student's response showed that the content was appropriate at 83.87% and the media was appropriate at 86.45%, both in the very appropriate category. This shows that local wisdom-based flipbook learning media is very suitable to be displayed in class.